Litigation and regulatory governance in the age of the Anthropocene: the case of fracking in the Karoo. (2nd April 2020) - Murcott, Melanie; Webster, Emily
ABSTRACT: The demand for fossil fuels, and most recently natural gas, has resulted in large-scale intervention with the Earth both from its extraction and its overwhelming contribution to global greenhouse gas emissions, and so climate change. Adopting a transnational legal methodology, this article assesses the role of non-state actors in the regulation of fracking in the ecologically and socially sensitive area of the Karoo, South Africa. The litigation discussed reveals a constellation of actors including the government and transnational fossil fuels promoting fracking on the one hand, and various non-state actors, such as civil society, domestic business as well as the global anti-fracking movement, opposing fracking on the other. The role and power of the state to regulate fracking is significantly impacted by these actors, including by refocussing the minds of transnational corporations and the state on the centrality of public participation, by challenging regulations introduced to govern fracking, and through delaying the operationalisation of fracking in the Karoo.